(untitled) (Scottish Historical and Archaeological Internet Reports, 2006)
Absolute dating for the great majority of deposits and structural remains encountered during 1981 and in the other investigations was lacking but it is possible to use the remains uncovered to present a clear and sustainable framework of the sequence of development in this area, linked to the historical and chronological framework of the rest of the building of St Giles.